Performance and Dividend Policy of State-Owned Banks Before and After COVID-19 - Artha, I Wayan Budi; Widyastuti, Tri; Gustari, Irvandi (Financial Risk and Management Reviews, 2022)
The purpose of this study was to analyze the performance and dividend policy of State-Owned Banks before and after the Covid-19. The research period is 2018-2021, with the sampling technique is saturated sampling, where all members of the population are used as samples. The analytical tool used is the Different Test (T-Test) supported by the SPSS program. The results show that the performance of State-Owned Banks, namely market capitalization, profitability, credit quality and liquidity is different before and after the Covid-19, while the dividend policy is not different. The market capitalization and profitability of State-Owned Banks have decreased and liquidity has improved after the Covid-19, as a result of deteriorating credit quality. Deteriorating credit quality after the Covid-19 resulted in decreased loan productivity and increased loss reserves and banks were more careful in distributing credit so that the liquidity was getting looser which resulted in decreased profitability.